Two new species of Kalcerrytus Galiano, 2000 (Araneae: Salticidae) from Tambopata River, Madre de Dios, Peru - Portuguez, Bryan (2021)
Jumping spiders of the genus Kalcerrytus inhabit the moist tropical forests of the Neotropical region. This genus includes 18 species, only both sexes are known for half of these and of K. leucodon only the female is known; the vast majority of species are registered for Brazil and there are records from Bolivia, Ecuador and French Guiana. Males are characterized by having a robust palp and more sclerotized than in other genera of the Freyina subtribe; females are distinguished by their broad epigynum with large funnel-shaped copulation openings and oblique edges. Two new species are herein described, and they represent the first record of the genus in Peru. Kalcerrytus mapinguari sp. nov. and Kalcerrytus yacuruna sp. nov. were collected in the Tambopata River region, which is characterized by its highly biodiverse tropical lowland evergreen forests. Illustrations of both male and female genitalia are provided as well as maps recording their distribution.